2021
DOI: 10.3389/fchem.2021.703710
|View full text |Cite
|
Sign up to set email alerts
|

Electron-to Hole Transport Change Induced by Solvent Vapor Annealing of Naphthalene Diimide Doped with Poly(3-Hexylthiophene)

Abstract: Herein we report on fabrication and properties of organic field-effect transistors (OFETs) based on the spray-coated films of N,N′-dioctyl naphthalene diimide (NDIC8) doped with 2.4 wt% of poly (3-hexylthiophene) (P3HT). OFETs with the untreated NDIC8:P3HT films revealed electron conductivity [μe* = 5 × 10–4 cm2×(Vs)−1]. After the annealing in chloroform vapor the NDIC8:P3HT films revealed the hole transport only [μh* = 0.9 × 10–4 cm2×(Vs)−1]. Due to the chemical nature and energy levels, the hole transport wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Obviously, because of unequilibrated crystal morphology and a mismatch between gold work function (−5.1 eV) and HOMO/LUMO levels of NDIs (approx. −7.2 eV/−3.6 eV, respectively), our methodology did not allow reaching the highest possible μ e or the lowest possible threshold voltage (V th ) numbers [ 20 , 70 , 71 , 73 ]. On the other hand, however, our approach enabled a direct comparison between all NDIs in the studied range.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Obviously, because of unequilibrated crystal morphology and a mismatch between gold work function (−5.1 eV) and HOMO/LUMO levels of NDIs (approx. −7.2 eV/−3.6 eV, respectively), our methodology did not allow reaching the highest possible μ e or the lowest possible threshold voltage (V th ) numbers [ 20 , 70 , 71 , 73 ]. On the other hand, however, our approach enabled a direct comparison between all NDIs in the studied range.…”
Section: Resultsmentioning
confidence: 99%
“…The OFET based on the N,N′ -dicyclohexyl-2,6-naphthalene NDI revealed electron mobility reaching as high as 6 cm 2 × V −1 × s −1 [ 7 , 16 , 17 , 18 ]. NDIs have been successfully used to enhance the electronic performance of polymer-based OFETs [ 19 , 20 , 21 ]. Lithium-ion batteries with NDI-based electrodes revealed discharge potentials ranging from 2.3 to 2.9 V [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the intrinsic chemical structure of the polymers, involving side-chain steric hindrance and backbone coplanarity, ,, and processing factors, such as solvents, , coating methods, film drying speed, , and substrate modifications, , both are capable of bringing about profound alterations in molecular orientation. Melt-annealing (thermal annealing above the melting point with subsequent slow cooling) has been found to be a useful post-treatment to achieve dramatic orientation change, resulting in edge-on dominated films. In comparison, another routine post-treatment, solvent vapor annealing (SVA), has been commonly utilized to improve molecular ordering, but few considerations for its application in controlling molecular orientation. SVA offers remarkable advantages: simplicity, low cost, free of the possibility of thermal decomposition of semiconductor materials, and less restrictions in the choice of substrate . Moreover, the interactions between the annealing solvent and polymers, including solvent–side chain and solvent–backbone interactions, could be expected to serve as an effective driving force for molecular reorientation. Thus, SVA is a promising candidate to achieve an orientation transition.…”
Section: Introductionmentioning
confidence: 99%